Combined MSC and GLP-1 Therapy Modulates Collagen Remodeling and Apoptosis following Myocardial Infarction - Elizabeth J. Wright; Nigel W. Hodson; Michael J. Sherratt; Moustapha Kassem; Andrew L. Lewis; Christine Wallrapp; Nadim Malik; Cathy M. Holt (Stem Cells International)
Background. Mesenchymal stem cells (MSCs) and glucagon-like peptide-1 (GLP-1) are being tested as treatment strategies for myocardial infarction (MI); however, their mechanisms in the heart are not fully understood. Methods. We examined the effects of MSCs, either native, or engineered to secrete a GLP-1 fusion protein (MSCs ± GLP-1), on human cardiomyocyte apoptosis in vitro. The effect on cardiac remodeling when encapsulated in alginate beads (CellBeads-MSC and CellBeads-MSC + GLP-1) was also evaluated in a pig MI model, whereby pigs were treated with Empty Beads, CellBeads-MSC, or CellBeads-MSC + GLP-1 and sacrificed at one or four weeks following MI. Results. MSC + GLP-1 conditioned media demonstrated antiapoptotic effects on ischaemic human cardiomyocytes in vitro. In vivo, qRT-PCR revealed large changes in the expression of several genes involved in extracellular matrix remodeling, which were altered following MSC ± GLP treatment. After four weeks, infarcted areas were imaged using atomic force microscopy, demonstrating significant alterations between groups in the structure of collagen fibrils and resulting scar. Conclusions. These data demonstrate that MSCs ± GLP-1 exhibit modulatory effects on healing post-MI, affecting both apoptosis and collagen scar formation. These data support the premise that both MSCs and GLP-1 could be beneficial in MI treatment.